2001
DOI: 10.1074/jbc.m106541200
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Model and Characterization of the Iron Stress-induced CP43′-Photosystem I Supercomplex Isolated from the Cyanobacterium Synechocystis PCC 6803

Abstract: The cyanobacterium Synechocystis PCC 6803 has been subjected to growth under iron-deficient conditions. As a consequence, the isiA gene is expressed, and its product, the chlorophyll a-binding protein CP43, accumulates in the cell. Recently, we have shown for the first time that 18 copies of this photosystem II (PSII)-like chlorophyll a-binding protein forms a ring around the trimeric photosystem I (PSI) reaction center (Bibby, T. S., Nield, J., and Barber, J. (2001) Nature, 412, 743-745). Here we further char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
107
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 39 publications
13
107
0
Order By: Relevance
“…3b). By overlaying the outlines for the PSII dimer of cyanobacterial PSII and for CP43 based on x-ray models [the latter as an analog of a Pcb protein (15,30)], the large particles are seen to consist of a core dimer with a f lanking region accommodating five Pcb proteins along each edge, making a total of 10 Pcb subunits per PSII dimer (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3b). By overlaying the outlines for the PSII dimer of cyanobacterial PSII and for CP43 based on x-ray models [the latter as an analog of a Pcb protein (15,30)], the large particles are seen to consist of a core dimer with a f lanking region accommodating five Pcb proteins along each edge, making a total of 10 Pcb subunits per PSII dimer (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the pcb gene sequence was similar to that of the gene that encodes the Chl a-binding protein CP43 of photosystem II (PSII) and the IsiA protein induced in cyanobacteria under conditions of limiting iron levels (12,13). Recent studies (14)(15)(16) have shown that the CP43-like IsiA protein forms a ring of 18 subunits around the cyanobacterial trimeric photosystem I (PSI) reaction center core complex. In so doing it increases the light-harvesting capacity of PSI by Ϸ80%.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…4) and the accumulation of a major chlorophyll a-binding protein, the isiA gene product CP43Ј that forms an 18-subunit ring around the trimeric PS-I core. Spectroscopic evidence suggests that CP43Ј is functionally coupled to PS-I reaction centers, indicating that it may act as a peripheral light-harvesting antenna (5,6). In the green alga Chlamydomonas reinhardtii, iron deprivation is associated with remodeling of PS-I, resulting in changes in the polypeptide composition of LHC-I and in a decreased efficiency of energy transfer between the light harvesting and reaction center (RC) (7,8).…”
mentioning
confidence: 99%